2020
DOI: 10.30994/sjik.v9i2.353
|View full text |Cite
|
Sign up to set email alerts
|

The Impact Analysis of Fire Disaster at Tamangapa, Makassar

Abstract: This research is a type of qualitative research using a descriptive phenomenological approach. This research aims to determine the impact of the fire disaster of the Tamangapa garbage dumpsite, Makassar. The results of the analysis showed that the health impacts that people felt were coughing, shortness of breath, dizziness, headaches and sore eyes. The environmental impact felt by the community is the presence of smoke, smog and foul odors. The social impact felt by the community is reduced income and schools… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Thus, it is also indicated that the high landfill temperature was probably influenced by the meteorological condition in 2018. The Landsat data used in this study for the year 2018 was also acquired before the landfill fire due to the hot climate in October [15]. However, in this study, meteorological data was not collected.…”
Section: Landfill Surface Temperaturementioning
confidence: 99%
“…Thus, it is also indicated that the high landfill temperature was probably influenced by the meteorological condition in 2018. The Landsat data used in this study for the year 2018 was also acquired before the landfill fire due to the hot climate in October [15]. However, in this study, meteorological data was not collected.…”
Section: Landfill Surface Temperaturementioning
confidence: 99%